A study of the sooting behavior of hydro-processed renewable jet and petroleum jet fuels in a laminar counter-flow flame. (1st May 2021) - Hsieh, Hsiang-Chun; Chen, Xiang-Xin; Faruq Alhikami, Akhmad; Wang, Wei-Cheng
Highlights: Soot formation of HRJ and petroleum jet fuels have been studied. The soot particle morphology of the fuels was characterized using TEM. The order of soot volume fraction: JP-5 > Jet-A1 > HRJ. The fuel with higher H/C ratio has lower soot volume fraction. Abstract: In this study, the soot formation behavior of hydro-processed renewable jet and petroleum jet fuels (Jet-A1, and JP-5) was investigated using a laminar counter-flow diffusion flame. Laser-induced incandescence was utilized to measure the soot volume fraction. The soot particle morphology of the fuels was characterized using transmission electron microscopy (TEM). It was found that the highest soot volume fraction was obtained in the following order: JP-5 > Jet-A1 > HRJ. Modifications to the reactant concentrations were observed to strongly influence the soot volume fraction by as much as 81%, 60%, and 64% for HRJ, JP-5, and Jet A1, respectively, and led to an increase in the soot particle diameter by as much as 26%, 15% and 10% for HRJ, JP-5, and Jet-A1, respectively. Both petroleum jet fuels reported soot particle diameters that were double those of the HRJ fuels. The fuel with higher H/C ratio (i.e. HRJ) had the lowest soot volume fraction. The smoke point results were found to have a positive correlation with the soot volume fraction for all of the tested fuels.